ANALISIS PENERAPAN KURIKULUM 2013 DI TK PEMBINA 5 PALEMBANG - Annisa, Tiara; Ramadhanti, Suci; Arianti, Rensintia; Hayuni, Trisia; Maharani, Tria; Aulia Putri, Rianti; Oktamarina, Lidia (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
This research aims to determine the planning, organization, implementation and evaluation or assessment of the implementation of the 2013 curriculum in the Pembina 5 Palembang State Kindergarten. The method used in this research is a descriptive qualitative method, namely a method aimed at describing or explaining the results of the research. Data collection techniques were carried out by examining the results of interview observations and documentation. In implementing teaching and learning activities at Pembina 5 Kindergarten, the K13 curriculum is used. The curriculum implementation program is the first learning plan, namely the preparation of the learning program, consisting of the preparation of the semester program. Weekly activity program and daily activity program. Second, teaching and learning activities consist of opening activities, core activities and closing activities. The aim of the curriculum and learning is to help children reach their developmental stages so it needs to be planned so that the goals can be achieved effectively and efficiently. Observations are carried out periodically and on a schedule, the results of group observations.